2015
DOI: 10.3122/jabfm.2015.s1.150087
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Staffing, Scheduling, and Engagement Strategies Among Primary Care Practices Delivering Integrated Care

Abstract: Purpose: To examine the interrelationship among behavioral health clinician (BHC) staffing, scheduling, and a primary care practice's approach to delivering integrated care.Methods: Observational cross-case comparative analysis of 17 primary care practices in the United States focused on implementation of integrated care. Practices varied in size, ownership, geographic location, and integrated care experience. A multidisciplinary team analyzed documents, practice surveys, field notes from observation visits, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…[15][16][17] We previously documented the extensive processes used by diverse community mental health centers and primary care practices to integrate behavioral and primary care in the Advancing Care Together (ACT) demonstration project. 15,16,18 -27 The ACT evaluation showed that the shift to integrated care requires extensive health system redesign, including modifications to team composition,and interprofessional interaction, 19 and that variations in approaches have implications for the cost of the health system redesign 29 and how well these efforts actually reach target patients. 30 This body of work established clear and compelling evidence that community practices modify evidence-based integration approaches to fit their local context.…”
mentioning
confidence: 99%
“…[15][16][17] We previously documented the extensive processes used by diverse community mental health centers and primary care practices to integrate behavioral and primary care in the Advancing Care Together (ACT) demonstration project. 15,16,18 -27 The ACT evaluation showed that the shift to integrated care requires extensive health system redesign, including modifications to team composition,and interprofessional interaction, 19 and that variations in approaches have implications for the cost of the health system redesign 29 and how well these efforts actually reach target patients. 30 This body of work established clear and compelling evidence that community practices modify evidence-based integration approaches to fit their local context.…”
mentioning
confidence: 99%
“…The consideration and tracking of reach to plan and fine tune interventions such as behavioral health integration is a fundamental skill for practices, and one that practice support organizations must begin to foster. 21 As is well described in the Article by Davis et al, 20 the planning of patient scheduling and patient transitions is inescapably intertwined with decisions regarding patient identification. Although integrated behavioral health care models promote brief, primary care, problem-focused interventions and warm handoffs between clinicians, most behavioral health clinicians are trained in and more comfortable with traditional behavioral health interventions, with longer appointments with patients referred by the primary care clinician.…”
Section: Care Processes and Structuresmentioning
confidence: 99%
“…The establishment of norms with staff and patients that interruptions are acceptable and permitted even while the behavioral health clinician is in the room with a patient also helps maintain availability. 20 Scheduling behavioral health clinicians in traditional blocks for more intensive, traditional counseling has advantages in billing and predictable scheduling, with little or no down time for the clinicians. However, this model results in limited ability for warm handoffs, consultations, or brief interventions and predominantly works in a referral framework.…”
Section: Care Processes and Structuresmentioning
confidence: 99%
“…Health professions educators may spot opportunities to improve their graduates' preparation for integrated practice. Davis et al 20 report details of staffing ratios and scheduling patterns and expose observed consequences to clinicians, staff, and patients attributable to the number and types of clinicians, their locations, and their occasional or constant availability. Cifuentes et al 21 go past the usual complaints about electronic health records (EHRs) to reveal observed workarounds deployed by practices to cope with the data collection and sharing requirements of integrated care.…”
mentioning
confidence: 99%